Geograficidade das mães universitárias do curso de licenciatura em educação do campo, da Universidade Federal Rural do Semi-Árido - Costa, Joelma Regina de Morais (Universidade Federal Rural do Semi-Árido, 2019)
The opportunity for women to go to higher education and to enter the job market has been greater, as there are many daily tasks and opportunities. Through higher education aimed at the people of the countryside, many women have the dream of graduating, the same as they had for years without studying, resurfaced. However, people have children and work, plus a responsibility and difficulties faced. This research aims to investigate the challenges and difficulties of academic and academic education in the field of UFERSA. The research was conducted through questionnaires in 14 students’ of the Health Sciences / Campus Mossoró course, with open, half-closed and closed questions, asking about the difficulties and particularities of each university student. Most students have been studied to study, have their children, work and study to support their homes, relating to what is more important than higher education in higher education. There are many difficulties, but they are mainly a lack of financial resources and family support for childcare and home care, but they are getting around situations and seeking their dr
Monografia
Keywords: Educação do campo; Mulher; Ensino; Field Education; Challenges; Difficulty; Conquest; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL